Negative pole piece, secondary battery, electric device, negative active material and preparation method of negative active material
By using a negative electrode active material including the first artificial graphite and the second artificial graphite, the negative electrode film layer structure of the secondary battery is solved, and the problem that existing secondary batteries are difficult to take into account both high energy density and dynamic performance is achieved, and better battery performance is achieved.
Patent Information
- Application Number
- CN202411214813.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-04-18
AI Technical Summary
It is difficult for existing secondary batteries to take into account high energy density and excellent kinetic performance.
Using a negative electrode active material including the first artificial graphite and the second artificial graphite, the structure of the negative electrode film layer is optimized by adjusting the powder OI value and powder compaction density to improve the energy density and kinetic performance of the secondary battery.
The secondary battery has high energy density and excellent dynamic performance, which improves the overall performance of the battery.
Smart Images

Figure CN119852318A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a negative electrode plate, a secondary battery, an electrical device, a negative electrode active material and a preparation method thereof. Background Art
[0002] In recent years, as the application scope of secondary batteries has become more and more extensive, secondary batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. With the rapid development of secondary batteries, people have also put forward higher requirements for their energy density and kinetic performance.
[0003] Therefore, how to make secondary batteries have high energy density and excellent dynamic performance has become an urgent problem to be solved in the field. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a negative electrode plate, a secondary battery, an electrical device, a negative electrode active material and a preparation method thereof, thereby enabling the secondary battery to have high energy density while also having excellent dynamic performance.
[0005] In order to achieve the above-mentioned object, the first aspect of the present application provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, wherein the negative electrode film layer comprises a negative electrode active material, wherein the negative electrode active material comprises a first artificial graphite and a second artificial graphite, the first artificial graphite comprises primary particles, the second artificial graphite comprises secondary particles, the powder OI value of the negative electrode active material is 2.5-6.5; the powder compaction density of the negative electrode active material under a pressure of 50000N is 1.75g / cc-1.94g / cc. The present application adopts a negative electrode active material comprising the first artificial graphite and the second artificial graphite, so that the secondary battery has both excellent dynamic performance and high energy density.
[0006] In some embodiments, the powder OI value of the negative electrode active material is 2.8-6.3, which is beneficial to improve the kinetic performance of the secondary battery.
[0007] In some embodiments, the powder compaction density of the negative electrode active material under a pressure of 50000 N is 1.79 g / cc-1.85 g / cc, which is beneficial to improve the energy density of the secondary battery.
[0008] In some embodiments, the gram capacity of the negative electrode active material is 353 mAh / g-359 mAh / g. By making the gram capacity of the negative electrode active material within the above range, it is beneficial to improve the energy density of the secondary battery.
[0009] In some embodiments, the negative electrode active material has a gram capacity of 354.6 mAh / g to 356.8 mAh / g.
[0010] In some embodiments, the graphitization degree of the negative electrode active material is 93.5%-95.5%. By making the graphitization degree of the negative electrode active material within the above range, it is beneficial to improve the energy density of the negative electrode active material.
[0011] In some embodiments, the graphitization degree of the negative electrode active material is 93.7%-95.3%.
[0012] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the negative electrode active material is 0.95-1.3; and / or the volume distribution particle size Dv50 of the negative electrode active material is 10.0 μm-15.5 μm. This is conducive to the negative electrode film layer having a suitable pore distribution, thereby improving the dynamic performance of the secondary battery.
[0013] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the negative electrode active material is 0.95-1.25; and / or the volume distribution particle size Dv50 of the negative electrode active material is 11.0 μm-14.5 μm. This is conducive to further improving the dynamic performance of the secondary battery.
[0014] In some embodiments, in the negative electrode active material, the volume distribution of particles with a particle size greater than 6.5 μm and less than 22.5 μm accounts for greater than or equal to 75%. By making the volume distribution of the negative electrode active material within the above range, it is beneficial to improve the cycle performance of the secondary battery. In some embodiments, in the negative electrode active material, the volume distribution of particles with a particle size greater than 6.5 μm and less than 22.5 μm accounts for 75%-90%.
[0015] In some embodiments, in the negative electrode active material, the mass ratio of the first artificial graphite to the second artificial graphite is 1:9 to 3:7. By making the mass ratio of the first artificial graphite to the second artificial graphite within the above range, it is beneficial for the negative electrode active material to have good kinetic performance, high energy density and good cycle performance. In some embodiments, in the negative electrode active material, the mass ratio of the first artificial graphite to the second artificial graphite is 1:9 to 1:3.
[0016] In some embodiments, the volume distribution particle size Dv50 of the first artificial graphite is 7 μm-9 μm, and Dv1 is 3 μm-5.5 μm. By making the volume distribution particle size of the first artificial graphite within the above range, it is beneficial to improve the dynamic performance of the secondary battery and increase the energy density.
[0017] In some embodiments, the OI value of the first artificial graphite powder is 7 to 10. When the OI value of the first artificial graphite powder is within the above range, it is beneficial to improve the dynamic performance of the secondary battery.
[0018] In some embodiments, the gram capacity of the first artificial graphite is 354.1 mAh / g-359.6 mAh / g. By making the gram capacity of the first artificial graphite within the above range, it is beneficial to improve the energy density of the secondary battery.
[0019] In some embodiments, the powder compaction density of the first artificial graphite is 1.72 g / cc-1.92 g / cc under a pressure of 50000 N. By making the powder compaction density of the first artificial graphite within the above range, it is beneficial to improve the energy density of the secondary battery.
[0020] In some embodiments, the volume distribution particle size Dv50 of the second artificial graphite is 13 μm-18 μm, which is beneficial to the dynamic performance of the secondary battery.
[0021] In some embodiments, the powder OI value of the second artificial graphite is 2 to 5. By making the powder OI value of the second artificial graphite within the above range, it is beneficial to improve the dynamic performance of the secondary battery.
[0022] In some embodiments, the gram capacity of the second artificial graphite is 353.0 mAh / g-358.2 mAh / g. By making the gram capacity of the second artificial graphite within the above range, it is beneficial to improve the energy density of the secondary battery.
[0023] In some embodiments, the second artificial graphite has a powder compaction density of 1.75 g / cc to 1.95 g / cc at a pressure of 50000 N. By making the powder compaction density of the second artificial graphite within the above range, it is beneficial to increase the compaction density of the negative electrode film layer, thereby increasing the energy density of the secondary battery.
[0024] The second aspect of the present application also provides a secondary battery, comprising the negative electrode plate provided in the first aspect of the present application. Therefore, the secondary battery of the present application has excellent dynamic performance and high energy density.
[0025] The third aspect of the present application further provides an electric device, comprising the secondary battery provided in the second aspect of the present application. Since the electric device of the present application comprises the secondary battery provided in the present application, it has at least the same advantages as the secondary battery.
[0026] The fourth aspect of the present application also provides a negative electrode active material, the negative electrode active material includes a first artificial graphite and a second artificial graphite, the first artificial graphite includes primary particles, the second artificial graphite includes secondary particles, the powder OI value of the negative electrode active material is 2.5-6.5; the powder compaction density of the negative electrode active material under a pressure of 50000N is 1.75g / cc-1.94g / cc. The present application adopts a negative electrode active material including the first artificial graphite and the second artificial graphite, so that the negative electrode film layer has both excellent dynamic performance and high energy density.
[0027] In some embodiments, the graphitization degree of the negative electrode active material is 93.5%-95.5%. By making the graphitization degree of the negative electrode active material within the above range, it is beneficial to improve the energy density of the negative electrode active material.
[0028] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the negative electrode active material is 0.95-1.3. By making the particle size distribution of the negative electrode active material within the above range, it is beneficial for the negative electrode film layer to have a suitable pore distribution, thereby improving the dynamic performance of the secondary battery. In some embodiments, the volume distribution particle size Dv50 of the negative electrode active material is 10.0μm-15.5μm. By making the volume distribution particle size Dv50 of the negative electrode active material within the above range, it is beneficial to improve the dynamic performance of the secondary battery.
[0029] The fifth aspect of the present application also provides a method for preparing a negative electrode active material, comprising the following steps:
[0030] The first artificial graphite preparation step: crushing and shaping the first raw material with a sulfur content of less than or equal to 1.5% by mass, grading and screening, and then graphitizing it at 3000° C.-3200° C. to prepare primary particles as the first artificial graphite;
[0031] The second artificial graphite preparation step is: crushing and shaping the second raw material with a sulfur content of less than or equal to 1.5% by mass to obtain primary particles, then adding a binder to granulate, and graphitizing at 3000° C.-3200° C. to obtain secondary particles as the second artificial graphite;
[0032] Mixing step: mixing the first artificial graphite and the second artificial graphite to obtain the negative electrode active material; wherein the powder OI value of the negative electrode active material is 2.5-6.5, and the powder compaction density of the negative electrode active material under a pressure of 50000N is 1.75g / cc-1.94g / cc.
[0033] The negative electrode active material prepared by the preparation method of the present application is beneficial to improving the kinetic performance of the secondary battery and to increasing the energy density of the secondary battery.
[0034] In some embodiments, in the first artificial graphite preparation step, a first graphitization is performed to prepare primary particles with a volume distribution particle size Dv50 of 7 μm-9 μm and Dv1 of 3 μm-5.5 μm as the first artificial graphite. This is conducive to improving the kinetic performance of the secondary battery and increasing the energy density.
[0035] In some embodiments, in the preparation step of the second artificial graphite, the second raw material is crushed and shaped to obtain primary particles with a volume distribution particle size Dv50 of 7μm-9μm; then a binder is added for granulation, and a second graphitization is performed at 3000℃-3200℃ to obtain secondary particles with (Dv90-Dv10) / Dv50 of 1.0-1.25 and Dv50 of 13μm-18μm, thereby obtaining the second artificial graphite. This is beneficial to improving the dynamic performance of the secondary battery.
[0036] In some embodiments, the first raw material and the second raw material may be the same or different.
[0037] In some embodiments, the mass percentage of sulfur in the first raw material and / or the second raw material is ≤0.6%, and the mass percentage of volatile components is ≤7%. By making the sulfur content and volatile components of the raw materials within the above range, it is beneficial to increase the graphitization degree of the negative electrode active material, thereby improving the energy density of the secondary battery.
[0038] In some embodiments, in the second artificial graphite preparation step, the softening point of the binder is ≥150° C. In some embodiments, the softening point of the binder is 150° C.-280° C. By using a binder with a softening point within the above range, it is beneficial to increase the gram capacity of the negative electrode active material and improve the energy density of the secondary battery.
[0039] In some embodiments, in the second artificial graphite preparation step, the amount of the binder added is 8%-14% relative to the mass of the primary particles. By making the amount of the binder added within the above range, it is beneficial to achieve better bonding and improve the isotropy of the secondary particles.
[0040] In some embodiments, in the mixing step, the ratio of the first artificial graphite to the second artificial graphite is 1: 9 to 3: 7. By making the ratio of the first artificial graphite to the second artificial graphite within the above range, it is beneficial for the negative electrode active material to have good kinetic performance, high energy density and good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a schematic diagram of a battery cell according to an embodiment of the present application.
[0042] Figure 2 yes Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown.
[0043] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.
[0044] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0045] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0046] Figure 6 Schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.
[0047] Figure 7 This is a scanning electron microscope image of the negative electrode active material of Example 1 of the present application.
[0048] Description of reference numerals:
[0049] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly; 6 primary particles; 7 secondary particles DETAILED DESCRIPTION
[0050] Below, the negative electrode sheet, secondary battery, electrical device, negative electrode active material and preparation method thereof of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0051] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0052] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0053] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0054] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0055] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.
[0056] If not otherwise specified, the values of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.
[0057] If not otherwise specified, in the present application, the term "active ions" refers to ions that can be intercalated and extracted back and forth between the positive electrode and the negative electrode of a secondary battery, including but not limited to lithium ions.
[0058] At present, in order to obtain secondary batteries with high kinetics, there are reports proposing to treat graphite materials by surface coating, etc. However, the use of surface coating means leads to a decrease in the material's gram capacity and the compaction density of the pole piece, affecting the energy density of the secondary battery. In addition, there are also reports proposing to use mixed silicon materials (including nano-silicon, silicon oxide, silicon-carbon composite materials, etc.) as negative electrode active materials to improve kinetics, but the volume expansion rate of silicon materials is large, which easily causes the negative electrode active material particles to pulverize and deteriorate the performance of the secondary battery. Therefore, it is difficult for current secondary batteries to have both high energy density and good kinetic performance.
[0059] In view of the above situation, the present application provides a negative electrode plate, a secondary battery, an electrical device, a negative electrode active material and a preparation method thereof, thereby enabling the secondary battery to have both high energy density and excellent kinetic performance.
[0060] Negative electrode
[0061] The present application provides a negative electrode plate, comprising a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, the negative electrode film layer comprising a negative electrode active material, the negative electrode active material comprising a first artificial graphite and a second artificial graphite, the first artificial graphite comprising primary particles, the second artificial graphite comprising secondary particles, the powder OI value of the negative electrode active material is 2.5-6.5; the powder compaction density of the negative electrode active material under a pressure of 50000N is 1.75g / cc-1.94g / cc.
[0062] In the present application, the powder OI value of the negative electrode active material is 2.5-6.5, which is conducive to improving the isotropy of the negative electrode active material, and the active ions can be deintercalated from all directions, thereby increasing the number of deintercalation channels of the active ions in the negative electrode active material particles, which is conducive to improving the dynamic performance of the secondary battery. In addition, the powder compaction density of the negative electrode active material under a pressure of 50000N is 1.75g / cc-1.94g / cc, which is conducive to improving the compaction density of the negative electrode film layer and improving the energy density of the secondary battery.
[0063] The present application adopts a negative electrode active material including a first artificial graphite and a second artificial graphite, which is beneficial to adjusting the powder OI value of the negative electrode active material and the powder compaction density under a pressure of 50000N, so that the negative electrode film layer has both excellent kinetic performance and high energy density.
[0064] In the present application, the negative electrode active material includes a first artificial graphite and a second artificial graphite, the first artificial graphite includes primary particles, and the second artificial graphite includes secondary particles. By making the negative electrode active material include primary particles of the first artificial graphite and secondary particles of the second artificial graphite, it is beneficial to make the negative electrode active material have both excellent kinetic performance and high energy density.
[0065] In some embodiments, the first artificial graphite is mainly composed of primary particles, for example, more than 80% of the first artificial graphite particles are primary particles, and illustratively, 80%, 85% or 90% of the first artificial graphite particles are primary particles. The second artificial graphite is mainly composed of secondary particles, for example, more than 80% of the second artificial graphite particles are secondary particles, and illustratively, 80%, 85% or 90% of the second artificial graphite particles are secondary particles.
[0066] In some embodiments, the powder OI value of the negative electrode active material can be, for example, 2.5, 2.6, 2.7, 3.0, 3.2, 3.5, 3.7, 4.0, 4.2, 4.5, 4.7, 5.0, 5.2, 5.5, 5.7, 6.0, 6.2, 6.5 or a range between any two of them. In some optional embodiments, the powder OI value of the negative electrode active material is 2.8-6.3.
[0067] In some embodiments, the powder compaction density of the negative electrode active material under a pressure of 50000 N can be, for example, 1.75 g / cc, 1.76 g / cc, 1.77 g / cc, 1.78 g / cc, 1.79 g / cc, 1.80 g / cc, 1.81 g / cc, 1.83 g / cc, 1.85 g / cc, 1.87 g / cc, 1.89 g / cc, 1.90 g / cc, 1.92 g / cc, 1.94 g / cc, or a value between any two values thereof. In some optional embodiments, the powder compaction density of the negative electrode active material under a pressure of 50000 N is 1.79 g / cc-1.85 g / cc.
[0068] In some embodiments, the gram capacity of the negative electrode active material is 353mAh / g-359mAh / g, for example, it can be 353mAh / g, 354mAh / g, 355mAh / g, 356mAh / g, 357mAh / g, 358mAh / g, 359mAh / g or a value between the ranges formed by any two of them. By making the gram capacity of the negative electrode active material within the above range, it is beneficial to improve the energy density of the secondary battery. In some optional embodiments, the gram capacity of the negative electrode active material is 354.6mAh / g-356.8mAh / g.
[0069] In some embodiments, the degree of graphitization of the negative electrode active material is 93.5%-95.5%. By making the degree of graphitization of the negative electrode active material within the above range, it is beneficial for the negative electrode active material to have a high compaction density and gram capacity, thereby improving the energy density of the negative electrode active material. Exemplarily, the degree of graphitization of the negative electrode active material can be 93.5%, 93.6%, 93.8%, 94.0%, 94.2%, 94.5%, 94.8%, 95.0%, 95.2%, 95.5% or a value between the ranges consisting of any two of them. In some optional embodiments, the degree of graphitization of the negative electrode active material is 93.7%-95.3%.
[0070] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the negative electrode active material is 0.95-1.3, for example, it can be 0.95, 0.96, 0.97, 0.98, 0.99, 0.10, 0.11, 0.12, 0.13 or a value between the ranges consisting of any two of them. By making the particle size distribution (Dv90-Dv10) / Dv50 of the negative electrode active material within the above range, its particle uniformity is better, which is conducive to the negative electrode film layer having a suitable pore distribution, thereby improving the kinetic performance of the secondary battery. In some optional embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the negative electrode active material is 0.95-1.25.
[0071] In some embodiments, the volume distribution particle size Dv50 of the negative electrode active material is 10.0-15.5 μm, optionally, 10.5-15.0 μm, and then optionally 11.0-15.0 μm. By making the volume distribution particle size Dv50 of the negative electrode active material within the above range, it is beneficial to improve the transport performance of active ions and electrons, thereby further improving the kinetic performance of the secondary battery. Exemplarily, the volume distribution particle size Dv50 of the negative electrode active material can be 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12.0 μm, 12.5 μm, 13.0 μm, 13.5 μm, 14.0 μm, 14.5 μm, 15.0 μm, 15.5 μm or a value between the ranges consisting of any two of them. In some optional embodiments, the volume distribution particle size Dv50 of the negative electrode active material is 11.0 μm-14.5 μm.
[0072] In some embodiments, in the negative electrode active material, the volume distribution proportion of particles with a particle size greater than 6.5 μm and less than 22.5 μm is greater than or equal to 75%. By making the volume distribution proportion of the negative electrode active material within the above range, the particle size distribution of the negative electrode active material is uniform, which is conducive to improving the uniformity of lithium insertion in the negative electrode film layer, thereby improving the cycle performance of the secondary battery. Exemplarily, in the negative electrode active material, the volume distribution proportion of particles with a particle size greater than 6.5 μm and less than 22.5 μm can be 75%, 76%, 77%, 78%, 80%, 82%, 84%, 86%, 88%, 89%, 90%, 91%, 92% or a value between the ranges consisting of any two of them. In some optional embodiments, in the negative electrode active material, the volume distribution proportion of particles with a particle size greater than 6.5 μm and less than 22.5 μm is 75%-90%, optionally 78%-88%.
[0073] In some embodiments, in the negative electrode active material, the mass ratio of the first artificial graphite to the second artificial graphite is 1:9 to 3:7. By making the mass ratio of the first artificial graphite and the second artificial graphite within the above range, it is beneficial to adjust the powder OI value and the powder compaction density of the negative electrode active material, so that the negative electrode active material can take into account good kinetic performance and high energy density as well as good cycle performance. Exemplarily, the mass ratio of the first artificial graphite and the second artificial graphite can be 3:7, 1:3, 1:4, 5:17, 1:9 or a value between the ranges consisting of any two ratios thereof. In some optional embodiments, the mass ratio of the first artificial graphite and the second artificial graphite is 1:9 to 1:3. In an optional embodiment, the mass ratio of the first artificial graphite and the second artificial graphite is 1:3.
[0074] In some embodiments, the volume distribution particle size Dv50 of the first artificial graphite is 7.0μm-9.0μm, and Dv1 is 3μm-5.5μm. By making the volume distribution particle size Dv50 of the first artificial graphite 7.0μm-9.0μm, the particle size of the first artificial graphite is smaller, which is conducive to reducing the distance of the solid phase diffusion path of the active ions in the first artificial graphite, and improving the deintercalation rate of the active ions, thereby improving the kinetic performance of the secondary battery; by making the Dv1 of the first artificial graphite 3μm-5.5μm, it is conducive to increasing the number of active ions embedded in the first artificial graphite, thereby increasing the gram capacity of the negative electrode active material, and is conducive to improving the energy density of the secondary battery. In addition, the first artificial graphite is conducive to improving the stability and processing performance of the negative electrode active material, increasing the proportion of the negative electrode active material in the negative electrode film layer, thereby further improving the energy density of the negative electrode film layer. Illustratively, the volume distribution particle size Dv50 of the first artificial graphite is 7 μm, 7.5 μm, 8 μm, 8.5 μm, and 9.0 μm, and Dv1 is 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, and 5.5 μm.
[0075] In some embodiments, the OI value of the first artificial graphite powder is 7-10, for example, it can be 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10 or a range consisting of any two of them. When the OI value of the first artificial graphite powder is within the above range, it is beneficial to improve the kinetic performance of the secondary battery.
[0076] In some embodiments, the gram capacity of the first artificial graphite is 354.1mAh / g-359.6mAh / g, optionally, 354.5mAh / g-359.0mAh / g. By making the gram capacity of the first artificial graphite within the above range, it is beneficial to improve the energy density of the secondary battery. Exemplarily, the gram capacity of the first artificial graphite can be 354.1mAh / g, 354.5mAh / g, 355.5mAh / g, 356.0mAh / g, 356.5mAh / g, 357.0mAh / g, 357.5mAh / g, 358.5mAh / g, 359.0mAh / g, 359.6mAh / g or a value between the ranges consisting of any two of them.
[0077] In some embodiments, the powder compaction density of the first artificial graphite under a pressure of 50000N is 1.72g / cc-1.92g / cc, for example, 1.72g / cc, 1.75g / cc, 1.76g / cc, 1.77g / cc, 1.78g / cc, 1.79g / cc, 1.80g / cc, 1.81g / cc, 1.83g / cc, 1.85g / cc, 1.87g / cc, 1.89g / cc, 1.90g / cc, 1.92g / cc or a value between the ranges consisting of any two of them. By making the powder compaction density of the first artificial graphite within the above range, it is beneficial to increase the compaction density of the negative electrode film layer and improve the energy density of the secondary battery.
[0078] In some embodiments, the volume distribution particle size Dv50 of the second artificial graphite is 13.0 μm-18.0 μm, optionally, 13.5 μm-17.0 μm. By making the volume distribution particle size of the second artificial graphite within the above range, it is beneficial to improve the isotropy of the negative electrode active material, increase the number of deintercalation channels of active ions in the negative electrode active material, and help improve the transmission efficiency of active ions and electrons, thereby improving the kinetic performance of the secondary battery. Exemplarily, the volume distribution particle size Dv50 of the second artificial graphite can be 13.0 μm, 13.5 μm, 14.0 μm, 14.5 μm, 15.0 μm, 15.5 μm, 16.0 μm, 16.5 μm, 17.0 μm, 17.5 μm, 18.0 μm or a value between the ranges consisting of any two of them.
[0079] In some embodiments, the powder OI value of the second artificial graphite is 2-5, for example, it can be 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0 or a value between the ranges formed by any two of them. By making the powder OI value of the second artificial graphite within the above range, it is beneficial to improve the isotropy of the secondary particles, increase the number of active ion deintercalation channels, increase the active sites of the negative electrode active material, and thus improve the kinetic performance of the secondary battery.
[0080] In some embodiments, the gram capacity of the second artificial graphite is 353.0mAh / g-358.2mAh / g, optionally, 353.0mAh / g-358.0mAh / g. By making the gram capacity of the second artificial graphite within the above range, it is beneficial to increase the gram capacity of the negative electrode active material, thereby increasing the energy density of the secondary battery. Exemplarily, the gram capacity of the second artificial graphite can be 353.0mAh / g, 353.5mAh / g, 354.0mAh / g, 354.5mAh / g, 355.0mAh / g, 355.5mAh / g, 356.0mAh / g, 356.5mAh / g, 357.0mAh / g, 357.5mAh / g, 358.0mAh / g, 358.2mAh / g or a value between the ranges consisting of any two of them.
[0081] In some embodiments, the powder compaction density of the second artificial graphite at a pressure of 50000N is 1.75g / cc-1.95g / cc, for example, 1.75g / cc, 1.76g / cc, 1.77g / cc, 1.78g / cc, 1.79g / cc, 1.80g / cc, 1.81g / cc, 1.83g / cc, 1.85g / cc, 1.87g / cc, 1.89g / cc, 1.90g / cc, 1.92g / cc, 1.95g / cc or a value between the ranges consisting of any two of them. By making the powder compaction density of the second artificial graphite within the above range, it is beneficial to increase the compaction density of the negative electrode film layer, thereby increasing the energy density of the secondary battery.
[0082] In the present application, by making the negative electrode active material include the first artificial graphite with a smaller particle size and the second artificial graphite with a high degree of isotropy, the negative electrode active material can exert the characteristics of high capacity, high compaction density and excellent dynamic performance, so that the secondary battery has high energy density and excellent dynamic performance. In addition, the first artificial graphite with a smaller particle size can be filled in the gap between the secondary particles of the second artificial graphite in the negative electrode active material, play a role in supporting and dispersing the secondary particles, improve the structural stability and processing performance of the negative electrode active material, reduce the amount of dispersant and suspending agent in the negative electrode film layer, increase the active sites of the negative electrode active material, thereby improving the dynamic performance of the secondary battery, and increase the proportion of the negative electrode active material in the negative electrode film layer, thereby improving the energy density of the secondary battery.
[0083] In the present application, the powder OI value of a material (e.g., negative electrode active material, first artificial graphite, second artificial graphite, etc.) refers to the graphite orientation of the material, which describes the orientation consistency of crystals in graphite material particles, and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (e.g., Bruker D8 Discover) can be used for testing. The test can refer to JIS K 0131-1996 and JB / T 4220-2011 to obtain an X-ray diffraction pattern of a powder sample. According to OI value = I 004 / I 110 The powder OI value of the sample is calculated. 004 is the integrated area of the diffraction peak of the 004 crystal plane of crystalline carbon in the powder sample, I 110 is the integrated area of the diffraction peak of the crystalline carbon 110 crystal plane in the powder sample. In the X-ray diffraction analysis test of the present application, a copper target can be used as an anode target, and CuKα rays can be used as a radiation source with a wavelength of The scanning 2θ angle range was 20°-80°, and the scanning rate was 4° / min.
[0084] In the present application, the powder compaction density of the material (negative electrode active material, first artificial graphite, second artificial graphite, etc.) is the mass of the powder per unit volume under specified conditions. The powder compaction density can be measured using instruments and methods known in the art. For example, it can be measured with an electronic pressure testing machine (for example, a UTM7305 electronic pressure testing machine) with reference to GB / T 24533-2009. An exemplary test method is as follows: weigh 1 g of sample powder and add a bottom area of 1.327 cm 2 In the mold, the pressure is increased to 50000N, the pressure is maintained for 30s, and then the pressure is released and maintained for 10s. Then the powder compaction density of the material under the pressure of 50000N is recorded and calculated.
[0085] In the present application, the volume distribution particle sizes Dv1, Dv10, Dv50, and Dv90 of materials (such as negative electrode active materials, first artificial graphite, second artificial graphite, etc.) respectively represent the particle sizes corresponding to the cumulative volume distribution percentages of the materials reaching 1%, 10%, 50%, and 90%, which can be measured using instruments and methods known in the art. For example, it can be measured using a laser particle size analyzer with reference to GB / T19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0086] In the present application, the volume distribution percentage of particles with a particle size greater than 6.5 μm and less than 22.5 μm can be determined by the following method: The particle size can be measured using instruments and methods known in the art. For example, it can be measured with a laser particle size analyzer with reference to GB / T 19077-2016. The volume distribution percentage X corresponding to a particle size less than or equal to 6.5 μm and the volume distribution percentage Y corresponding to a particle size less than 22.5 μm are tested. The volume distribution percentage of particles with a particle size greater than 6.5 μm and less than 22.5 μm is calculated using the formula (YX)*100%.
[0087] In the present application, the gram capacity of the material (negative electrode active material, first artificial graphite, second artificial graphite, etc.) is the ratio of the capacitance that the active material can release to the mass of the active material, and can be tested by methods known in the art. An exemplary test method is as follows: the sample powder is mixed with a conductive agent, a binder and other optional additives in a certain mass ratio with a solvent to form a slurry; the prepared slurry is applied on the surface of the negative electrode current collector copper foil, and dried in an oven for use; the electrolytic salt is dissolved in an organic solvent to prepare an electrolyte of a certain concentration; then a metal lithium sheet is used as a counter electrode, a polyethylene (PE) film is used as a separator, and the electrolyte is assembled into a CR2430 button battery in an argon-protected glove box. After the button cell was left to stand for 12 hours, it was discharged at 0.15 mA constant current to 0.005 V at 25 ° C, left to stand for 10 minutes, and then discharged at 50 μA constant current to 0.005 V, left to stand for 10 minutes, and then discharged at 10 μA constant current to 0.005 V; then it was charged at 0.3 mA constant current to 2.0 V, and the charge capacity was recorded. The ratio of the charge capacity to the sample mass is the gram capacity of the corresponding material (e.g., negative electrode active material, first artificial graphite, second artificial graphite, etc.).
[0088] In the present application, the graphitization degree of a material (e.g., a negative electrode active material, a first artificial graphite, a second artificial graphite, etc.) and the proportion of carbon in the material in the form of a graphite structure can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (e.g., Bruker D8 Discover) can be used for testing. The test can refer to JIS K0131-1996 and JB / T 4220-2011 to obtain the average interlayer spacing d of the C(002) crystal plane in the material crystal structure. 002 Then according to the formula g = (0.344-d 002 ) / (0.344-0.3354)×100% to calculate the graphitization degree. In the above formula, d 002 It is the average interlayer spacing of the C(002) crystal plane in the material's crystal structure expressed in nanometers (nm).
[0089] In the present application, primary particles and secondary particles have the meanings known in the art. Primary particles refer to non-agglomerated particles. Secondary particles refer to agglomerated particles formed by the aggregation of two or more primary particles. Primary particles and secondary particles can be distinguished by using a scanning electron microscope (SEM) image. An exemplary test method is as follows: the secondary battery is discharged to the lower cut-off voltage at a current of 0.33C, left to stand for 30 minutes, and discharged to the lower cut-off voltage at a current of 0.1C. Then the secondary battery is disassembled, the negative electrode sheet is taken out, the negative electrode sheet is cleaned with DMC to remove the lithium salt, and dried. The cleaned negative electrode sheet is then immersed in NMP for ultrasonic treatment, and the copper foil is separated to obtain the negative electrode material. After the negative electrode material is dried, the negative electrode material is sintered at 350°C-500°C, then washed with water several times, and dried at 80°C to obtain the negative electrode active material. The negative electrode active material is adhered to the conductive glue, and the particle morphology is tested using a scanning electron microscope, wherein the primary particles are non-agglomerated particles, and the secondary particles are agglomerated particles formed by the aggregation of two or more primary particles.
[0090] Negative electrode active material and preparation method thereof
[0091] The present application also provides a negative electrode active material, which has the same characteristics as the negative electrode active material included in the above-mentioned negative electrode plate, and will not be described in detail here.
[0092] The method for preparing the negative electrode active material of the present application comprises the following steps:
[0093] The first artificial graphite preparation step: crushing and shaping the first raw material with a sulfur content of less than or equal to 1.5% by mass, grading and screening, and then performing a first graphitization at 3000° C.-3200° C. to prepare primary particles as the first artificial graphite;
[0094] The second artificial graphite preparation step: crushing and shaping the second raw material with a sulfur content of less than or equal to 1.5% by mass to obtain primary particles, then adding a binder to granulate, and performing a second graphitization at 3000° C.-3200° C. to obtain secondary particles as the second artificial graphite;
[0095] Mixing step: mixing the first artificial graphite and the second artificial graphite to obtain the negative electrode active material; wherein the powder OI value of the negative electrode active material is 2.5-6.5, and the powder compaction density of the negative electrode active material under a pressure of 50000N is 1.75g / cc-1.94g / cc.
[0096] In the present application, in the above-mentioned first artificial graphite preparation step and / or the second artificial graphite preparation step, the first graphitization and / or the second graphitization is carried out at 3000° C.-3200° C. Exemplarily, the first graphitization and / or the second graphitization can be carried out at a temperature of 3000° C., 3050° C., 3100° C., 3150° C., 3200° C., or a value between the ranges consisting of any two of the values thereof.
[0097] In the present application, the treatment time of the first graphitization and / or the second graphitization can be 4-60 hours. For example, when the raw material is low-sulfur needle coke, the graphitization temperature is 3100° C., and the graphitization time can be 12 hours, 24 hours, or 36 hours.
[0098] By mixing the first artificial graphite and the second artificial graphite, the primary particle size of the first artificial graphite is small, the powder compaction density is high, and the secondary particle isotropy of the second artificial graphite is high, so that the powder OI value of the negative electrode active material is 2.5-6.5, and the powder compaction density of the negative electrode active material under a pressure of 50000N is 1.75g / cc-1.94g / cc, which is conducive to exerting the characteristics of high capacity, high compaction density and excellent dynamic performance of the negative electrode active material, so that the secondary battery has high energy density and excellent dynamic performance. The first artificial graphite with a smaller particle size can be filled in the gap between the secondary particles of the second artificial graphite in the negative electrode active material, play a role in supporting and dispersing the secondary particles, improve the structural stability and processing performance of the negative electrode active material, reduce the amount of dispersant and suspending agent in the negative electrode film layer, increase the active sites of the negative electrode active material, thereby improving the dynamic performance of the secondary battery, and increase the proportion of the negative electrode active material in the negative electrode film layer, thereby improving the energy density of the secondary battery.
[0099] In some embodiments, in the first artificial graphite preparation step, a first graphitization is performed to prepare primary particles with a volume distribution particle size Dv50 of 7μm-9μm and Dv1 of 3μm-5.5μm as the first artificial graphite. In the first artificial graphite preparation step, a classifier is used to classify and prepare primary particles with a volume distribution particle size Dv50 of 7μm-9μm and Dv1 of 3μm-5.5μm. The particle size of the primary particles is small, which is beneficial to reduce the distance of the solid phase diffusion path of the active ions in the primary particles, and improve the deintercalation rate of the active ions, thereby improving the kinetic performance of the secondary battery; and the volume distribution particle size Dv1 of the primary particles is 3μm-5.5μm, which is beneficial to increase the number of active ions embedded in the primary particles, thereby increasing the gram capacity of the negative electrode active material, and is beneficial to improving the energy density of the secondary battery.
[0100] In some embodiments, in the preparation step of the second artificial graphite, the second raw material is crushed and shaped to obtain primary particles with a volume distribution particle size Dv50 of 7μm-9μm; then a binder is added for granulation, and a second graphitization is performed at 3000℃-3200℃ to obtain secondary particles with (Dv90-Dv10) / Dv50 of 1.0-1.25 and Dv50 of 13μm-18μm, thereby obtaining the second artificial graphite. In the preparation step of the second artificial graphite, preparing secondary particles with a Dv50 of 13μm-18μm is beneficial to improving the isotropy of the negative electrode active material, increasing the number of active ion deintercalation channels in the negative electrode active material, and improving the transmission efficiency of active ions and electrons, thereby improving the kinetic performance of the secondary battery.
[0101] In the present application, the first raw material and / or the second raw material may be raw materials known in the art that can be used to prepare artificial graphite, without particular limitation. Exemplarily, the first raw material and / or the second raw material may include one or more of petroleum coke, calcined petroleum coke, needle coke, calcined needle coke, asphalt coke, and metallurgical coke; optionally, the first raw material and / or the second raw material may include one or more of petroleum coke, needle coke, and calcined needle coke. In one embodiment, the first raw material and / or the second raw material is needle coke.
[0102] In some embodiments, the sulfur content of the first raw material and / or the second raw material is ≤0.6% by mass, and the volatile components are ≤7% by mass. Here, the so-called volatile components refer to volatile organic matter, such as alkanes, aromatic hydrocarbons, lipids, etc. The sulfur content and volatile components of the first raw material and / or the second raw material are within the above ranges, which is conducive to reducing impurities in the first artificial graphite and the second artificial graphite obtained, improving the graphitization degree of the negative electrode active material, and thus improving the energy density of the secondary battery.
[0103] In the present application, the grading and screening can be achieved by using equipment known in the art without particular limitation. In some embodiments, the grading and screening can be performed by using a classifier. Exemplarily, the classifier is selected from a cyclone classifier and an air flow classifier.
[0104] In the present application, the adhesive in the second artificial graphite preparation step can be a binder known in the art, without particular limitation. For example, the adhesive can include one or more of oily asphalt, coal-based asphalt, high molecular polymer, and the like.
[0105] In some embodiments, in the second artificial graphite preparation step, the softening point of the adhesive is ≥150° C. The softening point of the adhesive refers to the temperature at which the adhesive changes from a solid state to a softened state with a certain fluidity; in this application, the softening point can be tested using instruments and methods known in the art, for example, it can be measured with reference to GB / T4507-2014.
[0106] The use of a binder with a softening point within the above range has a high coking value and is easy to graphitize, which is beneficial to increase the powder compaction density of the second artificial graphite, thereby increasing the gram capacity of the negative electrode active material and the energy density of the secondary battery. In some optional embodiments, the softening point of the binder is 150°C-280°C. Exemplarily, the softening point of the above binder can be 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C or a value between the ranges consisting of any two of them.
[0107] In some embodiments, in the second artificial graphite preparation step, the mass percentage of the binder is 8%-14% relative to the mass of the primary particles. By making the mass of the binder within the above range, it is beneficial to achieve better bonding and improve the isotropy of the secondary particles. Exemplarily, in the secondary particles, the mass percentage of the binder can be 8%, 9%, 10%, 11%, 12%, 13%, 14% or a value between the ranges consisting of any two of them.
[0108] In some embodiments, in the mixing step, the ratio of the first artificial graphite to the second artificial graphite is 1:9 to 3:7. By making the mass ratio of the first artificial graphite and the second artificial graphite within the above range, it is beneficial to adjust the powder OI value and the powder compaction density of the negative electrode active material, so that the negative electrode active material can take into account good kinetic performance and high energy density as well as good cycle performance. Exemplarily, the mass ratio of the first artificial graphite and the second artificial graphite can be 3:7, 1:3, 1:4, 5:17, 1:9 or a value between the ranges consisting of any two ratios thereof. In some optional embodiments, the mass ratio of the first artificial graphite and the second artificial graphite is 1:9 to 1:3. In an optional embodiment, the mass ratio of the first artificial graphite and the second artificial graphite is 1:3.
[0109] Secondary battery
[0110] The present application also provides a secondary battery.
[0111] The term "secondary battery" mentioned herein refers to a battery cell, a battery module or a battery pack, which are described below.
[0112] Generally, a secondary battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0113] In addition, the secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.
[0114] Negative electrode
[0115] The secondary battery of the present application includes the negative electrode sheet of the present application as described above.
[0116] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0117] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0118] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0119] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PvA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0120] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0121] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0122] Positive electrode
[0123] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0124] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0125] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0126] In some embodiments, when the battery cell is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523)、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.1 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0127] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode active materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.
[0128] In the list of positive electrode active materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.
[0129] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PvDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0130] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0131] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0132] Electrolytes
[0133] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0134] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0135] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0136] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0137] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0138] Isolation film
[0139] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0140] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0141] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0142] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0143] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0144] The present application has no particular restrictions on the shape of the battery cell, which can be cylindrical, square or any other shape. For example, Figure 1 The battery cell 5 is a square structure as an example.
[0145] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a top cover assembly 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the top cover assembly 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0146] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0147] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0148] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0149] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0150] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0151] Electrical devices
[0152] In addition, the present application also provides an electric device, which includes a secondary battery provided in the present application. The secondary battery can be used as a power source for the electric device, or as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0153] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0154] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0155] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0156] Example
[0157] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0158] Preparation of the first artificial graphite
[0159] Materials 1-1
[0160] Step 1: The needle-shaped green coke (sulfur content of 0.5% and volatile matter of 5%) is crushed and shaped by a mechanical mill, and then classified by an air flow classifier to remove small particles to obtain a shaped material.
[0161] Step 2: The above-mentioned shaped material is graphitized in an Acheson graphitization furnace at a high temperature of 3100°C for 36 hours; the graphitized particles are sieved and demagnetized to obtain primary particles with a Dv50 of 7.0 μm and a Dv1 of 3.5 μm as the first artificial graphite (material 1-1).
[0162] Material 1-2 to Material 1-4 and Material 1-1' to Material 1-3'
[0163] The preparation methods of materials 1-2 to 1-4 and materials 1-1' to 1-3' are similar to those of material 1-1, except that the type of raw materials and the graphitization temperature are adjusted. The Dv1, Dv50, powder OI value, gram capacity and powder compaction density of the obtained materials 1-2 to 1-4 and materials 1-1' to 1-3' are the values shown in Table 1.
[0164] The above materials were tested according to the following method, and the results are shown in Table 1.
[0165] Volume distribution particle size test of materials :
[0166] Dv50 test: referring to GB / T 19077-2016 particle size distribution laser diffraction method, the test was carried out using Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0167] Dv1: Referring to GB / T 19077-2016 particle size distribution laser diffraction method, the test was carried out using Mastersizer 3000 laser particle size analyzer produced by Malvern Instruments Ltd., UK.
[0168] (Dv90-Dv10) / Dv50: Referring to GB / T 19077-2016 particle size distribution laser diffraction method, the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Ltd. of the United Kingdom was used to test the values of Dv90, Dv50 and Dv10 respectively, and the value of (Dv90-Dv10) / Dv50 was calculated.
[0169] Test of OI value of powder material :
[0170] According to the lattice parameter test method of artificial graphite in JB / T 4220-2011, the test was carried out using a Bruker D8Discover X-ray diffractometer, in which a copper target was used as the anode target and CuKα rays were used as the radiation source. The wavelength of the rays was The scanning 2θ angle range is 20°-80°, the scanning rate is 4° / min, and the integral area I of the diffraction peak of the crystalline carbon 004 crystal plane in the material is obtained. 004 , the integral area I of the diffraction peak of the 110 crystal plane of crystalline carbon in the material 110 , the powder OI adopts the formula OI value = I 004 / I 110 to calculate.
[0171] Test of Gram Capacity of Materials :
[0172] The prepared materials, conductive agent carbon black (Super P), binder polyvinylidene fluoride (PVDF) and solvent N-methylpyrrolidone (NMP) were mixed uniformly in a mass ratio of 91.6:1.8:6.6 to prepare a slurry; the prepared slurry was coated on the surface of the negative electrode current collector copper foil, dried in an oven and set aside; ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and LiPF6 was dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L; then a metal lithium sheet was used as a counter electrode, a polyethylene (PE) film was used as an isolation membrane, and the electrolyte was assembled into a CR2430 button cell in an argon-protected glove box. The button cell was left to stand for 12 hours. .
[0173] At 25°C, the button cell prepared above was first discharged at a constant current of 0.15 mA to 0.005 V, allowed to stand for 10 minutes, then discharged at a constant current of 50 μA to 0.005 V, allowed to stand for 10 minutes, and then discharged at a constant current of 10 μA to 0.005 V, and the first-cycle discharge capacity of the button cell was recorded; thereafter, the button cell was charged at a constant current of 0.3 mA to 2.0 V, and the first-cycle charging capacity of the button cell was recorded. The ratio of the charging capacity to the mass of the material is the gram capacity of the material.
[0174] Testing of the compacted density of powder materials :
[0175] Take a certain amount of powder and put it in a special compaction mold, then put the mold on the compaction density instrument, set the pressure to 50000N, and the thickness of the powder under the pressure (thickness after pressure relief) can be read on the equipment. The compaction density can be calculated through ρ=m / v.
[0176] Table 1
[0177]
[0178] Preparation of the second artificial graphite
[0179] Materials 2-1
[0180] Step 1: Use mechanical grinding to crush and shape needle-shaped green coke (sulfur content 0.5%, volatile matter 5%) to obtain primary particles with a Dv50 of 8.0 μm.
[0181] Step 2: Use oily asphalt with a softening point of 180°C as a binder and granulate the primary particles together through a granulation kettle to obtain granulated material. The amount of the binder added is 10% relative to the total weight of the primary particles.
[0182] Step 3: Graphitize the above-mentioned granulated material at a high temperature of 3100°C for 36 hours; screen and demagnetize the graphitized particles to obtain secondary particles with a Dv50 of 14.5 μm as the second artificial graphite (material 2-1).
[0183] Material 2-2 to Material 2-3 and Material 2-1' to Material 2-2'
[0184] The preparation methods of materials 2-2 to 2-3 and materials 2-1' to 2-2' are similar to those of material 2-1, except that by adjusting the selection of raw materials, raw material crushing particle size, granulation particle size and graphitization temperature, the Dv50, powder OI value, gram capacity and powder compaction density under a pressure of 50,000 N of materials 2-2 to 2-3 are obtained as shown in Table 2.
[0185] The particle size, OI value, gram capacity and powder compaction density of the material were tested using the same method as the first artificial graphite, and the test results are recorded in Table 2.
[0186] Table 2
[0187]
[0188] Example 1
[0189] (1) Preparation of negative electrode active materials
[0190] The first artificial graphite 1-1 and the second artificial graphite 2-1 were mixed at a mass ratio of 25:75 to obtain a negative electrode active material.
[0191] The particle size, OI value, gram capacity and powder compaction density of the negative electrode active material were tested using the same method as the first artificial graphite.
[0192] The obtained negative electrode active material was photographed by scanning electron microscopy (SEM). Figure 7 As shown. Figure 7 As can be seen from the figure, the negative electrode active material includes primary particles 6 and secondary particles 7, wherein the unaggregated single-sheet graphite material is the primary particle, for example Figure 7 The primary particles 6 are marked in the figure; the particles formed by the agglomeration of multiple single-piece graphite materials are secondary particles, such as Figure 7 The secondary particles are marked as 7.
[0193] (2) Preparation of negative electrode sheet
[0194] The negative electrode active material, conductive agent carbon black (Super P), thickener sodium carboxymethyl cellulose, and binder styrene butadiene rubber prepared above were fully stirred and mixed in an appropriate amount of solvent deionized water at a weight ratio of 97.4:1:0.7:0.9 to form a negative electrode slurry. The negative electrode slurry was applied on the negative electrode current collector copper foil by extrusion coating, and after drying and cold pressing, a negative electrode sheet was obtained.
[0195] (3) Preparation of positive electrode sheet
[0196] Lithium iron phosphate: conductive carbon black: PVDF = 96.2:2:1.8 was mixed in a mass ratio, and then solvent N-methylpyrrolidone was added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on both surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained.
[0197] (4) Preparation of lithium-ion batteries
[0198] Use 12μm polyethylene film as the separator
[0199] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0200] The positive electrode sheet and negative electrode sheet prepared above are placed in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then the electrode assembly is obtained by winding; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and a secondary battery is obtained after vacuum packaging, standing, forming, shaping and other processes.
[0201] Embodiment 2-9
[0202] The battery preparation methods of Examples 2-9 are similar to those of Example 1, except that, in the step of preparing the negative electrode active material, the types of the first artificial graphite and the second artificial graphite and the mass ratio of the first artificial graphite and the second artificial graphite are adjusted as shown in Table 3.
[0203] Comparative Example 1
[0204] The battery preparation method of Comparative Example 1 is similar to that of Example 1, except that only the first artificial graphite is used.
[0205] Comparative Example 2
[0206] The battery preparation method of Comparative Example 2 is similar to that of Example 1, except that, in the preparation step of the negative electrode sheet, only the second artificial graphite is used as the negative electrode active material. The inventors found that when the negative electrode sheet was prepared according to the method of Example 1, the negative electrode active material, the conductive agent carbon black (Super P), the thickener sodium carboxymethyl cellulose, and the binder styrene butadiene rubber were in a weight ratio of 97.4:1:0.7:0.9, the second artificial graphite agglomerated and could not be fully dispersed to form a uniform negative electrode slurry, and therefore could not be used to prepare the negative electrode sheet. In order to obtain a uniform negative electrode slurry, the inventors adjusted the negative electrode active material, the conductive agent carbon black (Super P), the thickener sodium carboxymethyl cellulose, and the binder styrene butadiene rubber to a weight ratio of 96.1:1:1.6:1.3.
[0207] Performance Testing
[0208] (1) Energy density
[0209] At 25°C, the secondary battery was charged to 3.65V at 1 / 3C constant current, then charged to 0.05C at 3.65V, left to stand for 5 minutes, and then discharged to 2.5V at 1 / 3C constant current, and the battery discharge energy was recorded. The battery discharge energy divided by the battery weight is the battery weight energy density, in Wh / kg. The measurement data is shown in Table 3.
[0210] (2) Rapid charging performance test of secondary batteries
[0211] At 25°C, the secondary battery was charged to 3.65V at a constant current of 0.33C, then charged to a current of 0.05C at a constant voltage, and after standing for 5 minutes, the secondary battery was discharged to 2.5V at a constant current of 0.33C, and its actual capacity was recorded as C0.
[0212] Then the secondary battery is charged with constant current at 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, 3.0C0 in sequence to 3.65V or 0V negative electrode cut-off potential (whichever is reached first). After each charge, it is discharged to 2.5V at 1C0. Record the SOC (State of Charge) at different charge rates to 10%, 20%, 30%, ..., 80%. The charge rate-negative electrode potential curve under different SOC states is drawn, and the charge rate corresponding to the negative electrode potential of 0V under different SOC states is obtained after linear fitting. The charge rate is the charging window under the SOC state, which is recorded as C10% SOC, C20% SOC, C30% SOC, C40% SOC, C50% SOC, C60% SOC, C70% SOC, C80% SOC respectively. The charging time T of the secondary battery from 10% SOC to 80% SOC (under the premise that the secondary battery does not precipitate lithium) is calculated according to the following formula, in min. The shorter the charging time, the better the kinetic performance of the secondary battery:
[0213] T=(60 / C10%SOC+60 / C20%SOC+60 / C30%SOC+60 / C40%SOC+60 / C50%SOC+60 / C60%SOC+60 / C70%SOC+60 / C80%SOC)×10%
[0214] The secondary batteries prepared in Examples 1-9 and Comparative Examples 1-2 were subjected to performance tests, and the results are shown in Table 3.
[0215] Table 3
[0216]
[0217] It can be seen from the data in Table 3 that compared with the secondary batteries prepared in Comparative Examples 1 to 2, in the secondary batteries prepared in Examples 1 to 6, the negative electrode active materials include the first artificial graphite and the second artificial graphite, and the energy density of the secondary battery is significantly improved, and the charging time is significantly shortened. The secondary battery provided in the embodiment of the present application can take into account both high energy density and excellent kinetic performance. The powder OI of the negative electrode active material in Comparative Example 1 is too high, resulting in reduced battery kinetic performance. In Comparative Example 2, only the second artificial graphite of secondary particles is used as the negative electrode active material, and the second artificial graphite is agglomerated and cannot be fully dispersed. In order to form a uniform negative electrode slurry, the amount of dispersant is increased, which leads to a decrease in the energy density of the secondary battery. In addition, due to the increase in the ratio of the dispersant, more active sites on the surface of the negative electrode active material are occupied by the dispersant, which also has an adverse effect on the kinetic performance.
[0218] Examples 10-14
[0219] The battery preparation methods of Examples 10-14 are similar to those of Example 1, except that, in the step of preparing the negative electrode active material, the types of the first artificial graphite and the second artificial graphite and the mass ratio of the first artificial graphite and the second artificial graphite are adjusted as shown in Table 4.
[0220] Table 4
[0221]
[0222] It can be seen from the data in Table 4 that, compared with Comparative Examples 1 and 2 in Table 3, the secondary batteries prepared in Examples 10-14, wherein the negative electrode active material comprises a first artificial graphite of primary particles and a second artificial graphite of secondary particles, improve the energy density, shorten the charging time, and can take into account both high energy density and excellent kinetic performance.
[0223] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, wherein the negative electrode film layer comprises a negative electrode active material, characterized in that: The negative electrode active material includes a first artificial graphite and a second artificial graphite, The first artificial graphite includes primary particles, and the second artificial graphite includes secondary particles. The powder OI value of the negative electrode active material is 2.5-6.5; The powder compaction density of the negative electrode active material under a pressure of 50000N is 1.75g / cc-1.94g / cc.
2. The negative electrode sheet according to claim 1, characterized in that: The powder OI value of the negative electrode active material is 2.8-6.
3.
3. The negative electrode sheet according to claim 1 or 2, characterized in that: The powder compaction density of the negative electrode active material under a pressure of 50000N is 1.79g / cc-1.85g / cc.
4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The gram capacity of the negative electrode active material is 353 mAh / g-359 mAh / g.
5. The negative electrode sheet according to claim 4, characterized in that: The gram capacity of the negative electrode active material is 354.6 mAh / g-356.8 mAh / g.
6. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: The graphitization degree of the negative electrode active material is 93.5%-95.5%.
7. The negative electrode sheet according to claim 6, characterized in that: The graphitization degree of the negative electrode active material is 93.7%-95.3%.
8. The negative electrode sheet according to any one of claims 1 to 7, characterized in that: The particle size distribution of the negative electrode active material (Dv90-Dv10) / Dv50 is 0.95-1.3; and / or The volume distribution particle size Dv50 of the negative electrode active material is 10.0 μm-15.5 μm.
9. The negative electrode sheet according to claim 8, characterized in that: The particle size distribution of the negative electrode active material (Dv90-Dv10) / Dv50 is 0.95-1.25; and / or The volume distribution particle size Dv50 of the negative electrode active material is 11.0 μm-14.5 μm.
10. The negative electrode sheet according to any one of claims 1 to 9, characterized in that: In the negative electrode active material, the volume distribution proportion of particles with a particle size greater than 6.5 μm and less than 22.5 μm is greater than or equal to 75%.
11. The negative electrode sheet according to claim 10, characterized in that: In the negative electrode active material, the volume distribution of particles with a particle size greater than 6.5 μm and less than 22.5 μm accounts for 75%-90%.
12. The negative electrode sheet according to any one of claims 1 to 11, characterized in that: In the negative electrode active material, the mass ratio of the first artificial graphite to the second artificial graphite is 1:9 to 3:
7.
13. The negative electrode sheet according to claim 12, characterized in that: In the negative electrode active material, the mass ratio of the first artificial graphite to the second artificial graphite is 1:9 to 1:
3.
14. The negative electrode sheet according to any one of claims 1 to 13, characterized in that: The volume distribution particle size Dv50 of the first artificial graphite is 7 μm-9 μm, and Dv1 is 3 μm-5.5 μm.
15. The negative electrode sheet according to any one of claims 1 to 14, characterized in that: The first artificial graphite satisfies at least one of the following characteristics: (1) The OI value of the first artificial graphite powder is 7-10; (2) The gram capacity of the first artificial graphite is 354.1 mAh / g-359.6 mAh / g; (3) The powder compaction density of the first artificial graphite under a pressure of 50,000 N is 1.72 g / cc to 1.92 g / cc.
16. The negative electrode sheet according to any one of claims 1 to 15, characterized in that: The volume distribution particle size Dv50 of the second artificial graphite is 13 μm-18 μm.
17. The negative electrode sheet according to any one of claims 1 to 16, characterized in that: The second artificial graphite satisfies at least one of the following characteristics: (1) The OI value of the second artificial graphite powder is 2-5; (2) The gram capacity of the second artificial graphite is 353.0 mAh / g-358.2 mAh / g; (3) The powder compaction density of the second artificial graphite under a pressure of 50,000 N is 1.75 g / cc to 1.95 g / cc.
18. A secondary battery, characterized in that: A negative electrode sheet comprising any one of claims 1-17.
19. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 18.
20. A negative electrode active material, characterized in that: The negative electrode active material includes a first artificial graphite and a second artificial graphite, The first artificial graphite includes primary particles, and the second artificial graphite includes secondary particles. The powder OI value of the negative electrode active material is 2.5-6.5; the powder compaction density of the negative electrode active material under a pressure of 50000N is 1.75g / cc-1.94g / cc.
21. The negative electrode active material according to claim 20, characterized in that: The graphitization degree of the negative electrode active material is 93.5%-95.5%.
22. The negative electrode active material according to claim 20 or 21, characterized in that: The particle size distribution of the negative electrode active material (Dv90-Dv10) / Dv50 is 0.95-1.3; and / or The volume distribution particle size Dv50 of the negative electrode active material is 10.0 μm-15.5 μm.
23. A method for preparing a negative electrode active material, characterized in that: The following steps are involved: The first artificial graphite preparation step: crushing and shaping the first raw material with a sulfur content of less than or equal to 1.5% by mass, grading and screening, and then performing a first graphitization at 3000° C.-3200° C. to prepare primary particles as the first artificial graphite; The second artificial graphite preparation step: crushing and shaping the second raw material with a sulfur content of less than or equal to 1.5% by mass to obtain primary particles, then adding a binder to granulate, and performing a second graphitization at 3000° C.-3200° C. to obtain secondary particles as the second artificial graphite; Mixing step: mixing the first artificial graphite and the second artificial graphite to obtain the negative electrode active material; wherein the powder OI value of the negative electrode active material is 2.5-6.5, and the powder compaction density of the negative electrode active material under a pressure of 50000N is 1.75g / cc-1.94g / cc.
24. The preparation method according to claim 23, characterized in that: In the first artificial graphite preparation step, a first graphitization is performed to produce primary particles with a volume distribution particle size Dv50 of 7 μm-9 μm and Dv1 of 3 μm-5.5 μm, as the first artificial graphite.
25. The preparation method according to claim 23 or 24, characterized in that: In the preparation step of the second artificial graphite, the second raw material is crushed and shaped to obtain primary particles with a volume distribution particle size Dv50 of 7μm-9μm; then a binder is added for granulation, and a second graphitization is carried out at 3000℃-3200℃ to produce secondary particles with (Dv90-Dv10) / Dv50 of 1.0-1.25 and Dv50 of 13μm-18μm as the second artificial graphite.
26. The preparation method according to any one of claims 23 to 25, characterized in that: The mass percentage of sulfur in the first raw material and / or the second raw material is ≤0.6%, and the mass percentage of volatile components is ≤7%.
27. The preparation method according to any one of claims 23 to 26, characterized in that: In the second artificial graphite preparation step, the softening point of the adhesive is ≥150°C.
28. The preparation method according to claim 27, characterized in that: In the second artificial graphite preparation step, the softening point of the adhesive is 150°C-280°C.
29. The preparation method according to any one of claims 23 to 28, characterized in that: In the second artificial graphite preparation step, the amount of the binder added is 8%-14% relative to the mass of the primary particles.
30. The preparation method according to any one of claims 23 to 29, characterized in that: In the mixing step, the ratio of the first artificial graphite to the second artificial graphite is 1:9 to 3:7.
Citation Information
Patent Citations
Secondary battery, device, artificial graphite, and preparation method
CN113207313A
Secondary battery, production method therefor, and device comprising same
CN113875048A
Secondary battery, method for preparing same, and battery module, battery pack and device including same
CN114747042A
Composite artificial graphite and preparation method thereof, and secondary battery and electric device containing composite artificial graphite
CN116724002A
Artificial graphite and preparation method thereof, and secondary battery and electric device containing artificial graphite
CN117355963A
Cited By
Negative electrode active material and preparation method thereof, secondary battery and electric device
CN122291518A
Negative electrode sheet, secondary battery, electric device, and negative electrode active material and preparation method therefor
WO2026045198A1